Predicting the potential for mineral scale precipitation in unconventional reservoirs due to fluid-rock and fluid mixing geochemical reactions. (15th January 2021) - Hakala, J. Alexandra; Paukert Vankeuren, Amelia N.; Scheuermann, Peter P.; Lopano, Christina; Guthrie, George D.
Graphical abstract: Highlights: Mineral scale can impact production during unconventional reservoir development. Agreement observed between experimental, field, and reaction path modeling results. Predictive geochemical models identified reservoir and wellbore mineral reactions. Model predictions can be used to design mineral scale prevention treatments. Abstract: Mineral precipitation within hydraulically fractured shale may affect fluid flow pathways and impact long-term hydrocarbon production. The ability to predict geochemical reactions causing problematic mineral precipitation will lead to active reservoir management strategies for improving production. Using the Marcellus Shale as a case study, laboratory experiments and reaction path modeling were applied to determine which reactions occur during hydraulic fracturing, shut-in, flowback, and production timeframes. Experimental results indicate that contact between fracturing fluid and shale will result in dissolution of primary minerals (carbonates, quartz, feldspars, kaolinite, chlorite, pyrite) and secondary mineral precipitation over time periods of less than one week. Precipitation of secondary carbonates, barite, iron oxides, feldspars, amorphous silica and clay is likely to occur within the reservoir during shut in and early flowback due to mixing between fracturing fluid and reservoir brine as based on modeling saturation indices using experimental fluid data. Reaction path modeling corroborates the dissolution and precipitation reactions observed experimentally. Comparison of the results to injected and produced waters from a Marcellus Shale well pad in Greene County, PA, USA, shows that the mineral reactions occur during the hydraulic fracturing, shut in, and early flowback periods. The results presented here demonstrate the value in applying experimental approaches to identify mineral precipitation/dissolution reactions that may significantly impact reservoir performance. The good agreement between geochemical models and experimental results provides confidence that numerical models can be applied to screen the potential fluid-mineral and fluid-mixing reactions in unconventional reservoirs that result in undesired mineral scale precipitation.